Soham
Answered

Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

Find k if (x-3) is a factor of [tex] k^{2} x^{2} -kx-2[/tex]. 

Sagot :

k can be (-1/3) or (2/3).
since (x-3) is a factor. if you put x=3 in the equation, it must be equal to zero. So the equation becomes (9k2 - 3k -2 = 0). if you solve this you will get k=(-1/3) and k=(2/3). You can substitute this k in the original equation and check, (x-3) is a factor.
[tex]w(x)=k^2x^2-kx-2\\\\(x-3)\ is\ a\ factor\ w(x)\ then\ w(3)=0.\\\\Substitute:\\\\k^2\cdot3^2-k\cdot3-2=0\\9k^2-3k-2=0\\9k^2-6k+3k-2=0\\3k(3k-2)+1(3k-2)=0\\(3k-2)(3k+1)=0\iff3k-2=0\ \vee\ 3k+1=0\\3k=2\ \vee\ 3k=-1\\\\\underline{\underline{k=\frac{2}{3}\ \vee\ k=-\frac{1}{3}}}[/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.